Microwave and Radio-Frequency Technologies in Agriculture. An Introduction for Agriculturalists and Engineers - Farrell, Peter (De Gruyter, 2015)
Humanity's ability to produce enough food is mostly due to adoption of new methods and technologies by the agricultural industries as they became available. New information, communication and high speed processing and precision agriculture technologies have the potential to transform the agricultural industry. These technologies incorporate radio-frequency and microwave radiation into their systems. This book presents an overview of how these technologies are being used in agricultural systems. The main purpose of the book is to provide a glimpse of what is possible and encourage practitioners in the engineering and agricultural industries to explore how radio-frequency and microwave systems might further enhance the agricultural industry. The authors have extensive experience in agricultural and microwave engineering, instrumentation and communication systems.